Analysis of physiological indicators specific to the cardiac system (Eurasian Research Bulletin, 2025)
The heart provides blood circulation. The heart is divided into the “left heart” and the “right heart”. Each of them consists of a ventricle and a chamber. The blood leaves the capillaries, flows to the right heart and goes to the lungs. The blood is saturated with oxygen in the lungs and returns to the left heart, which distributes the blood to the entire body. The movement of blood from the right heart to the left heart through the pulmonary blood vessels constitutes the pulmonary circulation, that is, the small blood circulation. The blood supply of the remaining organs is called the systemic circulation or the large blood circulation. These two sections combine to form a single circulatory system. The pumping of blood by the heart is carried out by successive relaxation (diastole) and contraction (systole) During diastole, the atria and ventricles fill with blood, and during systole, blood is ejected from the ventricles into the large arteries, the aorta and pulmonary artery. At the exit of these arteries from the heart, there are semilunar valves that prevent blood from returning to the heart